STUDENTPRENEURSHIP APPROACH FOR IMPROVING EDUCATION AND ECONOMY EFFECTIVENESS AT IBNU KASIM NAHDLATUL WATHAN BINTAN - Kamaruzaman Kamaruzaman; Firdaus Firdaus; Sudanto Sudanto; Ferri Yonantha; Oktavianingsih Oktavianingsih; Fadilatul Ayuningrum; Nur Khalishah; Nur Ramadhini (JURNAL EDUSCIENCE (JES), 2022)
The objective of this research is to analyze  the effectiveness of education and economy through studentpreneurship approach at Ibnu Kasim Nahdlatul Wathan Bintan Islamic Boarding School. Method of this research is descriptive qualitative through the deep interview of the respondents until the information well obtained and reach the objective. Based on the results of the study show that the studentpreneurship approach (which empowers students in running the productive/entrepreneurial sector) is proven to increase the effectiveness of education and the economy at the Ibnu Kasim Nahdlatul Wathan Bintan Islamic Boarding School in terms of learning comfort, satisfaction with learning outcomes and ease of financing, meeting needs and achieving welfare.Keywords: effectiveness; education; studentpreneurship; economy